Legal and systematic issues in the interim economic partnership agreements: Which way now? - Cosmas Milton Obote Ochieng (International Centre for Trade and Sustainable Development (ICTSD), 2009)
This issue paper, titled 'Legal and Systemic Contested issues in Economic Partnership Agreements (EPAs) and WTO Rules: Which Way Now?', and written by Dr Cosmas Milton Obote O'chieng, is a contribution to this process. The paper provides a legal analysis of some systemic issues regarding the relationship between the WTO and EPAs. Some of these issues include the following: The application of the Most Favourable Nation Clause, Article XXIV of GATT and its relationship with EPAs - The effects of the 'standstill' clause on bound or applied tariff rates applied to ACP countries by WTO members - The political and legal effects of the 'Non-Execution Clause' in EPAs - The articulation of the dispute settlement mechanisms of EPAs and their interactions with the WTO one. - The paper concludes with a series of legal recommendations that could be useful to all stakeholders in understanding the stakes involved in the EPA negotiations.
Keywords: 330